Clinical Text Mining Secondary Use of Electronic Patient Records - Dalianis, Hercules (Springer Nature, 2018)
Data Mining; Text Mining; Health Informatics; Health Care Information Systems; Medical Terminologies; Natural Language Processing; Text Analysis; Support Vector Machines